Pengukuran Nilai Selisih Error Tegangan Keluaran Catu Daya DC dengan Menggunakan Multimeter Digital dan Multimeter Analog pada Praktikum Laboratorium Dasar Elektronika dan Rangkaian Listrik Jurusan Teknik Elektro Universitas Sriwijaya - Rachmat Firdaus Falka; Yahya Bahar (Jurnal Pengelolaan Laboratorium Pendidikan, 2022)
The power supply as a voltage source with a DC (Direct Current) output voltage or direct current is often used for electronic equipment, both office equipment and household equipment (Imam Saukani, 2020). In using the power supply, the output voltage is selected and high accuracy is required to obtain the output voltage that suits the user's needs. Often times, the power supply used in the practicum does not produce the right output voltage. The purpose of this study is to determine the value of the difference in the output voltage error generated after first determining the voltage value to be used at no-load using a digital multimeter and an analog multimeter as a comparison. After measuring the output voltage of the power supply, the correct voltage value is obtained in each practicum, measurements made at the same time can give definite results of the value of the output voltage of the power supply, the relatively small difference in results ensures that the power supply is in good condition, the output voltage of the power supply is measured using the measuring instrument with repeated measurements 7 (seven) times at each predetermined voltage and obtained a difference of 0.01V – 0.02V. After taking measurements using digital and analog multimeters, it can be concluded that measurements made before the practicum by measuring the output voltage of the power supply can help get the correct voltage value in each practicum, measurements by comparing measuring instruments at the same time can provide definite results of the resulting voltage value by the power supply, the difference in the results obtained is relatively small so as to ensure that the power supply is in good condition, the power supply can be used on loads or electronic equipment that requires a DC voltage source (Genta Subni Ananda Putra, et al, 2020). Practicum can be done well by measuring the output voltage of the power supply. This difference in output voltage results is what the author uses as research material for scientific writing which aims to find solutions to existing errors.